2009
DOI: 10.1590/s1516-89132009000100024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the construction of the harbor at pecém (Ceará, Brazil) upon reef fish communities in tide pools

Abstract: This study aimed to assess the impact of harbor construction at Pecém (Brazil)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The similarity matrix was calculated using the Sørensen index, and the clusters generated by the hierarchical agglomerative method using the UPGMA amalgamation strategy. The seven areas included in this study were: (1) Ceará -CE (present study; Araújo et al, 2000;Cunha et al, 2007Cunha et al, , 2008Freitas et al, 2009); (2) Maranhão -MA (Rocha & Rosa, 2001;Nunes et al, 2011a, b); (3) Risca do Zumbi RN -ZU (Feitoza, 2001); (4) Paraíba -PB (Rocha et al, 1998;Souza et al, 2007;Honório et al, 2010); (5) Abrolhos -AB (Moura et al, 2006); (6) Atol das Rocas (Rocas Atoll) -AR (Rosa & Moura, 1997;Floeter et al, 2008); and (7) Arquipélago de São Pedro e São Paulo (St Paul's Rocks) -SPSP (Lubbock & Edwards, 1981;Feitoza et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity matrix was calculated using the Sørensen index, and the clusters generated by the hierarchical agglomerative method using the UPGMA amalgamation strategy. The seven areas included in this study were: (1) Ceará -CE (present study; Araújo et al, 2000;Cunha et al, 2007Cunha et al, , 2008Freitas et al, 2009); (2) Maranhão -MA (Rocha & Rosa, 2001;Nunes et al, 2011a, b); (3) Risca do Zumbi RN -ZU (Feitoza, 2001); (4) Paraíba -PB (Rocha et al, 1998;Souza et al, 2007;Honório et al, 2010); (5) Abrolhos -AB (Moura et al, 2006); (6) Atol das Rocas (Rocas Atoll) -AR (Rosa & Moura, 1997;Floeter et al, 2008); and (7) Arquipélago de São Pedro e São Paulo (St Paul's Rocks) -SPSP (Lubbock & Edwards, 1981;Feitoza et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The final checklist of reef fish from Ceará, including the intertidal and subtidal zones, comprises both the species observed during the dives and those from the previous records available (Araújo et al, 2000;Cunha et al, 2007Cunha et al, , 2008Jucá-Queiroz et al, 2008;Freitas et al, 2009 ; Table 1. Details of the sampling sites, including depth, distance from the coast, geographic coordinates and type of reef (natural or artificial).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Microhabitat characteristics within rock pools might also be important for understanding the behaviour of different species and their interactions with environmental factors, such as pool dimensions and type of bottom (Lara & González, 1998; Gratwicke & Speight, 2005), which may vary according to wave exposure, tidal cycles and anthropogenic influence (Campbell & Pardede, 2006; Freitas et al , 2007; Cunha et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effects of habitat fragmentation by deepening of channels and removal of wetland vegetation in Lake Huron (Uzarski et al ., ), damage to commercial fisheries from marine sand mining in Korea (Kim & Grigalunas, ), the response of the fish community to the dredging operations of coastal rivers in the BioBio region in Chile (Ortiz‐Sandoval et al ., ), the response of tidal creek fishes to dredging and coastal development pressures in Lynnhaven River (Chesapeake Bay) (Bilkovic, ), interannual changes in benthic fish populations in the eastern region of the English Channel after sand and gravel mining (Drabble, ), and harbour construction effects on reef fish communities in north‐east Brazil (Freitas et al ., ), are types of indicators reported. Experiments evaluating the risks of prolonged exposure to high concentrations of suspended sediment (SS) in orange‐spotted grouper Epinephelus coioides (Hamilton 1822), an important mariculture species that has a wide distribution in the Indo‐Pacific, showed that damages to gill structure were evident and strongly correlated with SS concentration (Au et al ., ).…”
Section: Introductionmentioning
confidence: 99%